2017
DOI: 10.1159/000464476
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Vadadustat in Patients with Anemia Secondary to Stage 3 or 4 Chronic Kidney Disease

Abstract: Background: Therapeutic options for the treatment of anemia secondary to chronic kidney disease (CKD) remain limited. Vadadustat (AKB-6548) is an oral hypoxia-inducible factor prolyl-hydroxylase domain (HIF-PHD) inhibitor that is being investigated for the treatment of anemia secondary to CKD. Methods: A phase 2a, multicenter, randomized, double-blind, placebo-controlled, dose-ranging trial (NCT01381094) was undertaken in adults with anemia secondary to CKD stage 3 or 4. Eligible subjects were evenly randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 25 publications
13
112
0
Order By: Relevance
“…Following oral administration with vadadustat, eEPO levels returned to baseline within 24 h, similar to the expected physiological diurnal response [56].…”
Section: Vadadustatsupporting
confidence: 72%
See 1 more Smart Citation
“…Following oral administration with vadadustat, eEPO levels returned to baseline within 24 h, similar to the expected physiological diurnal response [56].…”
Section: Vadadustatsupporting
confidence: 72%
“…In contrast to roxadustat phase II studies, vadadustat administration has not been associated with a change in total cholesterol [56,57]. In phase II studies, it was well tolerated, Open label, randomized, 3-way, cross-over study to evaluate the relative bioavailability, PK, food effect, and palatability of the pediatric formulation versus adult tablet.…”
Section: Vadadustatmentioning
confidence: 99%
“…As with other HIF-PH inhibitors, the present study showed no change in plasma VEGF after enarodustat treatment [29,30]. AEs considered attributable to enhanced VEGF expression should be profiled in Phase 3 studies on the long-term safety of enarodustat.…”
Section: Discussion/conclusionmentioning
confidence: 49%
“…In Martin et al [18] study, after 6 weeks of every day dosing of HIF-PHI mean Hb increase of 0.76, 0.70, 1.15, and 1.39 g/dL from baseline with 240, 370, 500, and 630 mg doses, respectively, was observed. In Besarab et al [26] study with twice or thrice (TIW) in a week treatment for 4 weeks, mean Hb increase of 0.8-2.2 g/dL from baseline was observed with 0.7-2.0 mg/kg dose.…”
Section: Discussionmentioning
confidence: 91%
“…The activation of HIF promotes erythropoiesis through the stimulation of endogenous EPO production, increased uptake of iron, and mobilization of iron stores [18]. There are 3 isoforms of HIF (HIF-1, 2, and 3), of which HIF-1 and HIF-2 regulate the vascular response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%